Betatron Acceleration of Suprathermal Electrons within a Small-scale Flux Rope in the Solar Wind - Meng, Weiduo; Guo, Jianpeng; Lin, Haibo; Fu, Huishan; Zhou, Meng; Zhao, Dan; Chen, Yan; He, Linxia; Wang, Xianghan; Wang, Zelin (Astrophysical journal. Letters, 2023)
A growing body of evidence from observations, theories, and simulations indicates that particles can be effectively accelerated in solar wind regions filled with dynamic small-scale flux ropes (FRs). The main acceleration mechanisms identified in simulations include parallel electric field acceleration, first-order Fermi acceleration, and generalized betatron acceleration in contracting or merging small-scale FRs. However, direct identification of these acceleration mechanisms from in situ measurements remains a challenge. Here we present a distinct event of local betatron acceleration within a contracting small-scale FR in the solar wind, due to a local compression. In this event, the lower-energy halo electrons were effectively accelerated through the betatron mechanism, whereas the higher-energy suprathermal electrons predominated by the superhalo component were almost not energized. The halo electron energization processes via the betatron mechanism are reproduced using an analytical model. Further examination of small-scale FRs in the vicinity of the heliospheric current sheet over the period 1995–2020 indicates that in situ signatures of the betatron acceleration process are essentially elusive.